Health promotion and nurse facing newborn pain in the neonatal unit: an exploratory-descriptive study - Lélis, Ana Luiza Paula de Aguiar; Farias, Leiliane Martins; Rebouças, Cristiana Brasil de Alemida; Cardoso, Maria Vera Lúcia Moreira Leitão (Online Brazilian Journal of Nursing, 2010)
Introduction: Health promotion in neonatal intensive care unit (NICU) can be disclosed from the humanized care to the newborn. Objective:The objective was to analyze the nurse’s perception about the pain of the newborn through the VAS and PIPP scales during venipuncture. Method: Exploratory-descriptive study and observational, held in the NICU of a public hospital in Fortaleza-CE, in may/2010. The subjects were 19 newborns and 18 nurses, venipunctures totaled 54. The collect took place from the systematic observation and non-participatory. Results:There wasn’t equivalence in 68.5% of the responses between VAS and PIPP scales values, showing that the perception of nurses regarding pain in neonates is not associated with actual pain demonstrated. Implications on nursing: It’s necessary that nurses improve their knowledge about pain management and pain scales, thus leading to greater awareness about the pain in the newborn painful procedures.